Effect of Abrasive Waterjet Machining Parameters on Hybrid AA6061-B4C- CNT Composites. (2018) - Gnanavelbabu, A.; Saravanan, P.; Rajkumar, K.; Karthikeyan, S.; Baskaran, R.
Abstract: In general, Metal Matrix Composites (MMC)are very hard to machine using conventional machining due to complexity towards elevated temperature and tool wear issues. Abrasive water jet machining is a very efficient machining process which overcomes tool wear issues and cutting temperature issues. In this research study, AA6061-B4 C- CNT was machined using Abrasive Waterjet Machining under different process parameters such as mesh size, abrasive flow rate, pressure and traverse speed. Boron carbide was used as reinforcement and Carbon Nanotube (CNT) was used as a solid lubricant. Two different composition of boron carbide (5, 15 vol%) and CNT (5, 15vol%) with residual volume percentage of aluminium as a core material were fabricated using stir casting method. The Machining approach is based on the Taguchi L9 orthogonal array design to enhance the Abrasive waterjet process parameters effectively. Then the multiple responses were investigated such as kerf taper geometries (θ), surface roughness (Ra) and material removal rate (MRR). The features of different machined surface regions were studied using Scanning electron microscopy (SEM). The investigational results indicate that increasing reinforcement improves the kerf taper angle under the significant parameter of traverse speed and decreasing the reinforcement leads to the lower surface roughness under significant parameter of pressure and traverse speed. It was observed that increasing reinforcement increasing the Material Removal Rate under the significant contribution of reducing mesh size of abrasive particles and inclined velocity.